Regulation of Madness in Early Childhood Education: Exploring Undergraduates’ Understanding of Professional Identity and Mental Health - Davies, Adam; Greensmith, Cameron; Spring, Lauren; Adam, Simon; Richardson, Brooke; Rice, Carla; Smoliak, Olga; Menon, Nidhi; Purnell, Alexander; Beaton, John (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This qualitative study investigates how sanist systems of oppression within early childhood education both reflect and reinforce dominant discourses on mental health and madness. Through a Mad studies analysis of both qualitative interview data with postsecondary early childhood education and child studies students, as well as policy and curriculum documents relevant to Ontario postsecondary early childhood education studies, we seek to disrupt taken-for-granted assumptions and create space for mental difference. This study was conducted with 25 postsecondary early childhood education and child studies students, with the data analyzed using both Foucauldian and institutional ethnographic methods. Ultimately, this study illustrates how madness and Mad educators are constructed as a potential harm to the profession, reinforcing sanist forms of discrimination against educators with mental health differences.